Disease Specific Autoantibodies in Idiopathic Inflammatory Myopathies - Stuhlmüller, Bruno; Schneider, Udo; González-González, José-B.; Feist, Eugen (Frontiers in Neurology, 2019)
Idiopathic inflammatory myopathies represent still a diagnostic and therapeutic challenge in different disciplines including neurology, rheumatology, and dermatology. In recent years, the spectrum of idiopathic inflammatory myopathies has been significantly extended and the different manifestations were described in more detail leading to new classification criteria. A major breakthrough has also occurred with respect to new biomarkers especially with the characterization of new autoantibody-antigen systems, which can be separated in myositis specific antibodies and myositis associated antibodies. These markers are detectable in approximately 80% of patients and facilitate not only the diagnostic procedures, but provide also important information on stratification of patients with respect to organ involvement, risk of cancer and overall prognosis of disease. Therefore, it is not only of importance to know the significance of these markers and to be familiar with the optimal diagnostic tests, but also with potential limitations in detection. This article focuses mainly on antibodies which are specific for myositis providing an overview on the targeted antigens, the available detection procedures and clinical association. As major tasks for the near future, the need of an international standardization is discussed for detection methods of autoantibodies in idiopathic inflammatory myopathies. Furthermore, additional investigations are required to improve stratification of patients with idiopathic inflammatory myopathies according to their antibody profile with respect to response to different treatment options.